The Cosmic, Political, and Personal in late Ming Travel Narratives to the Home of Confucius. (3rd July 2017) - Sloane, Jesse
Abstract : Historians have tended to frame the history of Qufu and Queli as a sequence of state initiatives, or of contests among branches of the Kong clan and with the state. In travel accounts by late Ming literati, however, these efforts at self-promotion frequently met with indifference, skepticism, or derision. Visitors to Qufu showed more interest in the chance to encounter artifacts associated with Confucius and other figures from the classical era and the resulting sense of a personal connection with sagehood, often perceiving in the site a numinous power credited to geomantic or cosmological principles, the metaphysical effects of sagehood, and the actions of spirits. These various forces could all be accounted for within mainstream Neo-Confucian cosmology, but Ming travelers differed as to which prevailed at Qufu. The observations in this study suggest that the cultural history of Qufu during the Ming be broadened from its current focus on court-sponsored regulation and ritual to include narratives of spiritual and intellectual discovery by literati visiting individually and in voluntarily organized groups. More than state intervention and the maneuvering of local clans, these travelers may have played a leading role in defining the cultural importance of this Confucian sacred site in the literati society of the late Ming and after.